Ensuring Administrative Legality and Justice Through Judicial Review In Indonesia - Iristian, Yovan (Journal of International Multidisciplinary Research, 2024)
Within the context of the Indonesian legal system, this study investigates the crucial function that judicial review plays in ensuring that administrative procedures are lawful and that justice is served. This study sheds light on the techniques, processes, and issues that are involved with judicial review in relation to administrative acts. It does so by conducting a comprehensive analysis of judicial decisions, legal precedents, and legislative frameworks. The paper provides an in-depth analysis of the development of judicial review in Indonesia, following its historical progression and analysing the current state of affairs. Through an in-depth analysis of administrative decisions, it examines the role that the court plays in ensuring that administrative procedures are valid, preserving a system of checks and balances, and protecting fundamental rights. The impact of judicial review on administrative institutions and the legal landscape is also investigated in this study. Particular attention is paid to the role that judicial review plays in promoting openness, accountability, and adherence to the rule of law for administrations. The purpose of this research is to give useful insights into the efficient operation of Indonesia's administrative governance and the improvement of justice in administrative procedures. This is accomplished by casting light on the junction between judicial review and administrative law.